2000
DOI: 10.1016/s0734-743x(99)00151-7
|View full text |Cite
|
Sign up to set email alerts
|

Damage evolution, localization and failure of solids subjected to impact loading

Abstract: In order to reveal the underlying mesoscopic mechanism governing the experimentally observed failure in solids subjected to impact loading, this paper presents a model of statistical microdamage evolution to macroscopic failure, in particular to spallation. Based on statistical microdamage mechanics and experimental measurement of nucleation and growth of microcracks in an Al alloy subjected to plate impact loading, the evolution law of damage and the dynamical function of damage are obtained. Then, a lower bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…It has revealed that in ductile fracture, spallation occurs via nucleation, growth, and coalescence of microvoids, 4,5 while in brittle fracture, spallation occurs via nucleation, growth, and coalescence of microcracks. 6,7 Although the mechanism of spallation in conventional polycrystalline alloys is understood, the mechanism of spallation in bulk amorphous alloys is unclear. As a relatively young class of alloy materials, bulk amorphous alloys [8][9][10] have many excellent physical and mechanical properties such as high strength and hardness due to their unique microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…It has revealed that in ductile fracture, spallation occurs via nucleation, growth, and coalescence of microvoids, 4,5 while in brittle fracture, spallation occurs via nucleation, growth, and coalescence of microcracks. 6,7 Although the mechanism of spallation in conventional polycrystalline alloys is understood, the mechanism of spallation in bulk amorphous alloys is unclear. As a relatively young class of alloy materials, bulk amorphous alloys [8][9][10] have many excellent physical and mechanical properties such as high strength and hardness due to their unique microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Spallation is a typical process with coupled multiple space and time scales [13]. For the time-dependent damage process, which consists of microcrack nucleation and growth, Table 1 lists all parameters involved in the problem, with their corresponding dimensions L, T , and M are the notations of the dimensions of length, time, and mass, respectively.…”
Section: Damage Localization In An Al Alloy Under Impact Loadingmentioning
confidence: 99%
“…(9). For more details of DFD, one can refer to Bai et al [13] and Davison and Stevens [15]. M , S, De, and De * are four dimensionless parameters, as introduced above.…”
Section: Damage Localization In An Al Alloy Under Impact Loadingmentioning
confidence: 99%
“…These studies provide progressively helpful means to reveal the essence of spalling. In recent 10 years, some new and informative studies relevant to spallation are made to have deeper understanding of the process [7][8][9][10][11][12][13][14]. All these work intended to link the macroscopic spallation and the microdamage evolution inside materials.…”
Section: Introductionmentioning
confidence: 99%